MULTILINGUALISME PADA GENERASI Z DAN UPAYA PEMERTAHANAN BAHASA - Herdiani, Rizki; Amir, Johar; Satriani, Irma; Candra Dewi, Anita; Fitri, Sakinah (CENDEKIA: Jurnal Ilmu Pengetahuan, 2025)
Multilingualism is becoming increasingly prominent among Generation Z, who are growing up amid globalization and digital technological advancement. While many studies have separately examined language shift or language maintenance, few have specifically explored the relationship between multilingual practices among Generation Z and the preservation of regional languages, particularly in linguistically diverse areas such as South Sulawesi. This study aims to describe the patterns of first, second, and third language use among Generation Z and explore their connection to language maintenance efforts. Using a descriptive qualitative approach, data were collected through observation, questionnaires, and interviews with 60 respondents aged 18–20 from various regions in South Sulawesi. The findings reveal that 63.3% of respondents use Indonesian as their first language, followed by Bugis (18.3%), Makassarese (15%), and others. For the second language, respondents tend to use regional languages, while English dominates as the third language (65%). These results indicate a shift in regional languages from the position of mother tongue to second or third language. However, there is still evidence of preservation efforts through the use of regional languages within family and social settings. These findings provide a foundation for the formulation of linguistic and educational policies that promote regional language revitalization, and they enrich theoretical understanding of multilingual dynamics in the digital era. ABSTRAK Multilingualisme merupakan fenomena yang semakin menonjol di kalangan Generasi Z yang hidup di tengah arus globalisasi dan kemajuan teknologi digital. Meskipun banyak penelitian membahas pergeseran bahasa atau pemertahanan bahasa secara terpisah, masih sedikit yang mengkaji hubungan antara praktik multilingualisme Generasi Z dan pelestarian bahasa daerah, khususnya di wilayah dengan keragaman bahasa seperti Sulawesi Selatan. Penelitian ini bertujuan untuk menggambarkan pola penggunaan bahasa pertama, kedua, dan ketiga di kalangan Generasi Z serta mengeksplorasi keterkaitannya dengan upaya pemertahanan bahasa daerah. Menggunakan pendekatan deskriptif kualitatif, data diperoleh melalui observasi, angket, dan wawancara terhadap 60 responden usia 18–20 tahun dari berbagai daerah di Sulawesi Selatan. Hasil penelitian menunjukkan bahwa 63,3% responden menggunakan bahasa Indonesia sebagai bahasa pertama, disusul Bugis (18,3%), Makassar (15%), dan lainnya. Sebagai bahasa kedua, responden cenderung menggunakan bahasa daerah, sementara bahasa Inggris dominan sebagai bahasa ketiga (65%). Temuan ini menunjukkan adanya pergeseran bahasa daerah dari posisi bahasa ibu menjadi bahasa kedua atau ketiga. Namun, tetap terdapat indikasi upaya pelestarian melalui penggunaan bahasa daerah dalam lingkungan keluarga dan sosial. Temuan ini memberikan dasar bagi perumusan kebijakan linguistik dan pendidikan yang mendorong revitalisasi bahasa daerah, serta memperkaya pemahaman teoretis tentang dinamika multilingualisme di era digital.